Indicadores de qualidade e composição de leite informal comercializado na região Sudeste do Estado de São Paulo - Motta, Rodrigo G. [UNESP]; Silva, Aristeu V.; Giuffrida, Rogerio; Siqueira, Amanda K.; Paes, Antonio C. [UNESP]; Motta, Igor G.; Listoni, Fernando J. P. [UNESP]; Ribeiro, Marcio G. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2015)
The informal milk is recognized as the product marketed without inspection. We evaluated the microbiological quality, nutritional ingredients and substances inhibiting bacterial growth in 100 informal samples from cows milk, marketed in the southwest region of the state of Sao Paulo, Brazil. It was found that 77% of Somatic Cell Count (SCC) and 86% of Total Bacterial Count (TBC) of the samples were at odds with the maximum values required by Instruction Rules 62 of the Ministry of Agriculture and Livestock Supply. It was identified to solids contents in disagreement (36%), protein (23%), fat (38%), nonfat dry extract (43%) and 73% urea nitrogen. In 59% of the samples was detected residues of the bacterial growth inhibitors. Were isolated 240 strains of micro-organisms with a prevalence of enterobacteria, streptococci, staphylococci and fungi. The informal milk is marketed in the region without the minimum hygienic conditions and present risks to public health, and represents serious socio-economic problem for the region.

O leite informal é reconhecido como o produto comercializado sem inspeção. Avaliou-se a qualidade microbiológica, constituintes nutricionais e presença de substâncias inibidoras do crescimento bacteriano em 100 amostras informais de leite de vacas, comercializadas na região sudoeste do estado de São Paulo, Brasil. Verificou-se que 77% da Contagem de Células Somáticas (CCS) e 86% da Contagem Bacteriana Total (CBT) das amostras estavam em desacordo com os valores máximos exigidos pela Instrução Normativa 62 do MAPA. Identificaram-se teores em desacordo para sólidos totais (36%), proteína (23%), gordura (38%), extrato seco desengordurado (43%) e nitrogênio uréico (73%). Em 59% das amostras detectou-se a presença de resíduos de inibidores do crescimento bacteriano. Isolaram-se 240 linhagens de micro-organismos com predomínio de enterobactérias, estreptococos, estafilococos e fungos. O leite informal é comercializado na região sem as mínimas condições de higiene e oferece riscos a saúde pública, além de representar sério problema sócio-econômico para região.
Indicators of quality and composition of informal milk marketed in the in the Southeast region of São Paulo, Brazil
Keywords: Cow; Mastitis; Instruction Rules 62; Inhibitory; TBC; Cellularity; Informal milk; Vaca; Mastite; Instrução Normativa 62; Inibidores; CBT; Celularidade; Leite informal